2018
DOI: 10.1177/1753193418773329
|View full text |Cite
|
Sign up to set email alerts
|

Clinical measurement of the dart throwing motion of the wrist: variability, accuracy and correction

Abstract: Despite being functionally important, the dart throwing motion is difficult to assess accurately through goniometry. The objectives of this study were to describe a method for reliably quantifying the dart throwing motion using goniometric measurements within a healthy population. Wrist kinematics of 24 healthy participants were assessed using goniometry and optical motion tracking. Three wrist angles were measured at the starting and ending points of the motion: flexion–extension, radial–ulnar deviation and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…[25][26][27][28] PAMs, which can generate high power at low pressures, are well suited for mimicking natural gait movements, 26,27) as in the current DTSaM orthosis, and for providing powerassisted gloves. 29) The current DTSaM results are similar to those of a previous study, 30) and DTM movements may be closely reproduced. However, it takes time for the artificial muscle to expand after the pressure is applied to the entire rubber tube.…”
Section: Directionssupporting
confidence: 88%
“…[25][26][27][28] PAMs, which can generate high power at low pressures, are well suited for mimicking natural gait movements, 26,27) as in the current DTSaM orthosis, and for providing powerassisted gloves. 29) The current DTSaM results are similar to those of a previous study, 30) and DTM movements may be closely reproduced. However, it takes time for the artificial muscle to expand after the pressure is applied to the entire rubber tube.…”
Section: Directionssupporting
confidence: 88%
“…This seems to be a disadvantage for clinical application. Meanwhile, in 2018, Vardakastani et al 18 ) described a method that uses a conventional goniometer for measuring the functional DTM. In their report, goniometry was initially not able to quantify the range of DTM accurately, although a correction equation that takes values of flexion, extension and ulnar deviation angle measured simultaneously as input variables enables the measurement to be used with confidence as part of clinical assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Vardakastani et al found, using goniometric measurements in live healthy patients, the orientation of the dart-throwing motion plane relative to the flexion-extension axis ranged from 28°to 57°. 8 Crisco et al, using cadaveric arms, found that the wrist motion was oriented obliquely to the direction of pure flexion-extension by 26.6°AE 4.4°. 9 The largest wrist range of motion was a mean of 111.5°AE 10.2°, oriented 30°f rom pure flexion, in the direction of ulnar flexion.…”
Section: Introductionmentioning
confidence: 99%